Communication Strategies Employed by The ELT Students in Speaking Class - Rozal, Edi (JR-ELT (Journal of Research in English Language Teaching), 2017)
This study was aimed at identifying the communication strategies employed by the students in Speaking class and their reasons in employing communication strategies. The design of the research was descriptive case study. The result of the study shows that the students employed twelve communication strategies, namely, approximation strategy which was employed by the students 65 times, stalling for time-gaining 44 times, appeal for help 19 times, literal translation 15 times, code switching 13 times, message abandonment 10 times, topic voidance 7 times, word coinage twice, foreignizing once, use of non-linguistic signals once, repetition 25 times, and self-correction 5 times. Based on the data obtained from the interview, the researcher found that the students who used communication strategies said that they used communication strategies because of their nervousness, lack of vocabulary, lack of language structures, the influence of their L1. Moreover, the students said that they wanted to avoid the silence of speaking, to make the word clear to the listener and to correct their own mistakes.